Application of didactic resources in the teaching learning process of the English language for students of first and second year of bachillerato of Colegio Fiscal Tecnico Dr. Juan Henríquez Coello, in Machala city, academic year 2014-2015. - Mizhquiri Manzano, Eliana Belén; Reyes Suriaga, Jéssica Dolores; Rojas Bravo, Jenny María (Machala : Universidad Técnica de Machala, 2014)
El fenómeno de la globalización ha contribuido en gran manera a convertir al inglés en el idioma más importante y necesario de la actualidad, siendo entendido como el idioma de los países desarrollados, teniendo en alto índice de crecimiento alrededor del mundo.
The phenomenon of globalization has contributed greatly to make English the most important and necessary language currently being treated as the language of developed countries, given high rates of growth around the world.
Keywords: APPLICATION; LEARNING; ENGLISH LANGUAGE